2018
DOI: 10.4103/jlp.jlp_49_17
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and gastrointestinal cancer

Abstract: Vitamin D serves as a precursor to the potent steroid hormone calcitriol, which has widespread actions throughout the body. Calcitriol regulates numerous cellular pathways that could have a role in determining cancer risk and prognosis. Low Vitamin D levels have been implicated in numerous disease processes including fracture risk, falls, cardiovascular disease, hypertension, diabetes mellitus, and cancers. Metabolite of 1, 25-dihydroxyvitamin D3 (1,25[OH]2D3) regulates numerous genes that control gut physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Vitamin D is also noted to engage in a variety of physiological pathways including regulation of cell cycle, cellular proliferation, angiogenesis, apoptosis, and molecular cell signaling. This validates its participation in tumorigenic activity [ 9 ]. 1,25D3 binds to a specific vitamin D receptor (VDR), which is a member of the nuclear receptor superfamily.…”
Section: Introductionsupporting
confidence: 68%
“…Vitamin D is also noted to engage in a variety of physiological pathways including regulation of cell cycle, cellular proliferation, angiogenesis, apoptosis, and molecular cell signaling. This validates its participation in tumorigenic activity [ 9 ]. 1,25D3 binds to a specific vitamin D receptor (VDR), which is a member of the nuclear receptor superfamily.…”
Section: Introductionsupporting
confidence: 68%
“…The World Health Organization's International Agency for Research on Cancer has reported that there is a strong association between an individual's vitamin D level and the risk of colorectal cancer development and survival [47]. In addition, several observational studies have reported associations between low vitamin D levels and the incidence of, and mortality due to, CRC [48]. Mechanistic studies show that, through gene regulation, 1α,25-dihydroxyvitamin D3 or calcitriol (active vitamin D metabolite) inhibits the proliferation and promotes the epithelial differentiation of human colon carcinoma cell lines that express vitamin D receptors [49].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the hypothesis that combinations of vitamin A and D may be more effective than either vitamin alone in epithelial cell cancers, which may have significant clinical impact. It has been suggested that the anticancer effects of vitamin A and D may be mediated through their respective receptors [9,10]. Vitamin A (retinoids) are ligands for the…”
Section: Discussionmentioning
confidence: 99%